The construction of mathematical time functions for storm events - Mohd Arish @Arshad, Nur Aini (2003)
The main objective of applying statistics in rainfall analysis deals with interpreting a past record of rainfall events, the derivation of information from these observed past hydrologic phenomena and making inferences for the future purpose. Rainfall cannot be predicted with certainty. Therefore statistical analysis is important so that the information received is more easily to understand.The objective of this study is to construct the structure of the time functions of storm between storm and time functions of storm between peaks for Wilayah Persekutuan Kuala Lumpur. From this result, we can simulate or generate the information of time between storms and time between storm peaks. The data for this study was obtained from Department of Irrigation and Drainage of Wilayah Persekutuan Kuala Lumpur. The study area involved 13 stations. Rainfall data is from the year 2000 till 2001. Analysis was done using regression analysis. The data showed that all of them are nonlinear. Two models were used, the exponential model and logarithm model. Most of the results showed that logarithm model performed better result compared to exponential model. All analysis was done using Microsoft Excel.